Smart Empowerment: Innovative Construction of a Multi-Modal Blended Teaching System for College English - Li Zhou (Journal of Advanced Research in Education, 2025)
Grounded in the theory of multi-modal discourse analysis, this paper conducts an in-depth exploration of the current challenges encountered in college English smart teaching. Leveraging the online smart teaching platform, it maximizes the exploitation and utilization of multi-modal teaching resources, seamlessly integrates multidisciplinary knowledge, and actively pursues the online and offline integration of the college English smart teaching system. Initiating from the four dimensions of smart teaching environment creation, teaching mode construction, teaching method innovation, and teaching evaluation enhancement, a comprehensive and systematic overall design for college English multi-modal smart teaching will be executed. The aim is to fully propel the profound integration of information technology and college English teaching, break through the crucial bottlenecks in the implementation of “Internet + Education”, enhance the quality and effectiveness of college English teaching in an all-round and multi-level manner, furnish potent theoretical support and practical exemplars for the reform and development of college English teaching, and contribute to the realization of the talent cultivation objectives in higher education.